ANTIOXIDANT ACTIVITY OF PROTEIN HYDROLYSATE PRODUCED FROM TUNA EYE (Thunnus sp.) BY ENZYMATIC HYDROLYSIS - Dewi Mutamimah; Bustami Ibrahim; Wini Trilaksani (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2018)
Tuna (Thunnus sp.) by-products from frozen loin and canning industry especially the eye is rich in proteins and in lipids consisting of polyunsaturated fatty acids (PUFA). That requires protective agent (antioxidant) to inhibit the oxidation naturally present and predicted to be protein peptides. Enzymatic hydrolysis of protein is an appropriate method to produce bioactive peptide with such nutraceutical/pharmaceutical function such as an antioxidant peptide. This study aimed to produce protein hydrolysate having a function as anwith an antioxidant activity from eye of tuna through enzymatic hydrolysis and determining the antioxidant activity by DPPH methods. Protein soluble content of tuna’s eye protein hydrolysate (TEPH) ranged from 59.98±0.130 to 94.90±0.002%. The degree of hydrolysis (DH) of TEPH was about 9.10±0.28 to 16.14±0.09%. The highest inhibition of DPPH radical scavenging activity was 93.57±0.05% (at 5 mg/mL) was obtained with a DH of 11.35±0.002% at the concentration 0.1% of papain for 6 hours hydrolysis. The IC50 value of was 1.08±0.008 mg/mL